1980
DOI: 10.1038/288095a0
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of poly(I).poly(C)-induced human fibroblast interferon mRNA species

Abstract: Three classes of human interferons (IFNs) have been defined on the basis of their immunological properties: the 'Le' or 'alpha' IFN, mainly derived from leukocyte or lymphoblastoid cells; the 'F' or 'beta' IFN, mainly derived from fibroblast cultures; and the 'T', 'immune' or 'gamma' IFN, mainly derived from mitogen- or antigen-stimulated lymphoid cells. Whereas several individual species of Le IFN have been purified to homogeneity, it is generally considered that F IFN represents a single protein. Thus curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
85
1
2

Year Published

1981
1981
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(96 citation statements)
references
References 32 publications
8
85
1
2
Order By: Relevance
“…The mRNA is longer than the cloned cDNA (860 nucleotides) (14-16) due to the presence ofpoly(A) residues; an average length ofpoly(A) in most eukaryotic mRNAs is 250 nucleotides (24), which is in agreement with our findings. Others have estimated the mRNA to be 850-950 nucleotides long (19,20 our results do not confirm observations of Sagar et al (25), who found that / mRNA induced in Namalva cells is significantly larger than that in fibroblasts.…”
Section: Resultscontrasting
confidence: 56%
See 1 more Smart Citation
“…The mRNA is longer than the cloned cDNA (860 nucleotides) (14-16) due to the presence ofpoly(A) residues; an average length ofpoly(A) in most eukaryotic mRNAs is 250 nucleotides (24), which is in agreement with our findings. Others have estimated the mRNA to be 850-950 nucleotides long (19,20 our results do not confirm observations of Sagar et al (25), who found that / mRNA induced in Namalva cells is significantly larger than that in fibroblasts.…”
Section: Resultscontrasting
confidence: 56%
“…1). Because multiple forms of immunologically crossreacting / interferon were previously found (19,20), the pooled fractions were microinjected into Xenopus oocytes and the newly synthesized proteins were labeled with [3S]methionine. Interferon was identified by selective immunoprecipitation with antiserum to / interferon and analyzed by one-and two-dimensionalgel electrophoresis.…”
Section: Resultsmentioning
confidence: 99%
“…This protein can be precipitated with a partially purified antiserum directed against partially purified HuIFN-P. After cloning the corresponding cDNA [6] they could purify this mRNA on its cloned cDNA and translate it into a 23 -26-kDa-protein with antiviral and (2'-5')(A),, synthetase-inducing activities. This protein was named IFN-P, and is probably distinct [7] from the IFN-P, described by Sehgal et al [8,9]. We have also observed such a 26-kDa-protein mRNA in preparations of mRNA from poly (1).…”
supporting
confidence: 55%
“…The IFN-/32 gene is located on human chromosome 7 (9), and cloned IFN-/82 genomic DNA transfected into rodent cells yields cells that can be induced by poly(I)-poly(C) to produce biologically active human IFN-P2 (7,8). Although IFN-/31 and -/32 mRNAs do not cross-hybridize with the respective heterologous IFN-/3 cDNA probes, polyclonal and monoclonal antisera raised against IFN-,81 neutralize the anti-viral activity of IFN-P32 (3)(4)(5)(6)(7)(8)(9). IFN-f-related DNA has also been localized on human chromosomes 2 and 4 (14,15).…”
mentioning
confidence: 99%
“…Multiple distinct ,3 interferon (IFN-,B) genes are induced by poly(I)-poly(C) in human fibroblasts (3)(4)(5)(6)(7)(8)(9). The IFN-,/1 gene has been cloned and expressed as biologically active recombinant IFN-,81 (reviewed in refs.…”
mentioning
confidence: 99%